Genetic diversity and population structure analysis of Capsicum germplasm accessions - Xiao-zhen GU; Ya-cong CAO; Zheng-hai ZHANG; Bao-xi ZHANG; Hong ZHAO; Xiao-min ZHANG; Hai-ping WANG; Xi-xiang LI; Li-hao WANG (Journal of Integrative Agriculture, 2019)
Genetic diversity plays an essential role in plant breeding and utilization. Pepper is an important vegetable and spice crop worldwide. The genetic diversity of 1 904 accessions of pepper conserved at the National Mid-term Genebank for Vegetables, Beijing, China was analyzed based on 29 simple sequence repeat (SSR) markers, which were evenly distributed over 12 pepper chromosomes. The pepper accessions were divided into two groups in a genetic structure analysis, and the two groups showed obvious differences in fruit type and geographical distribution. We finally selected 248 accessions capturing 75.6% of the SSR alleles as the core collection for further research. Insights into the genetic structure of pepper provide the basis for population-level gene mining and genetic improvement.